PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DI SEKOLAH MENENGAH - Salmiati Salmiati; Zahnur Zahnur; Rini Oktavia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Information technology development has reached all aspects of life, including education. The use of technology in the learning process provides a big role and function for the world of education in providing interesting and easy to be accessed learning resources. This study aims to develop Android-based learning media on the lesson matrix for class XI, find the feasibility level of Android-based learning media according to validation results and find the level of acceptance of Android-based learning media in accordance with the results of testing on users. This study uses the Research and Development method. The steps include the analysis, design, development, implementation, and evaluation stages. The results showed that the learning media